Discourse and language education - Hatch, Evelyn (Cambridge [England]: New York : Cambridge University Press, 2001)
Discourse analysis is the study of how communication--spoken and written--is structured so that it is socially appropriate and linguistically accurate. This book gives practical experience in analyzing discourse. It includes analyses of spoken language--conversations, classroom interactions, speech events, and scripts--and written language--from formal rhetorical structures of composition to the informal style of personal letters. Because the organization of discourse differs across languages, example data are drawn from native speakers and language learners of all ages, backgrounds, and proficiency levels. Thus, Discourse and Language Education will be of great interest to teachers of ESL/EFL, foreign language teachers, and special education teachers, especially those working with the hearing impaired."--Jacket
Includes bibliographical references and index.
Keywords: Discourse analysis; Communication; Speech acts (Linguistics)